ТЕЗ АЙТИШ ЖАНРИ ТАБИАТИ ВА ЎРГАНИЛИШ ТАРИХИ - Мадияров, И.Б. (SCIENCE and SOCIETY, 2018)
The article deals with genre, of tongue-twister and pecularities, its world Folkloristics, also division to scientific-practical resourses have analyzed with concrete investigations. Also there have been analired comporisons of tongue-twisters in uzbek-karakalpak Folkloristics.